Molecular Cytogenetic Characterization of a Non-Robertsonian Dicentric Chromosome 14;19 Identified in a Girl with Short Stature and Amenorrhea - Usha R. Dutta; Vijaya Kumar Pidugu; Ashwin Dalal (Case Reports in Genetics)
We report a 16-year-old girl who presented with short stature and amenorrhea. Initially the cytogenetic analysis showed the presence of a mosaic non-Robertsonian dicentric chromosome involving chromosomes 14 and 19. Subsequent molecular cytogenetic analysis by fluorescence in situ hybridization (FISH) using whole chromosome paints, centromeric probes, as well as gene specific probes confirmed the dicentric nature of the derivative chromosome and indicated that the rearrangement involved the short arms of both of these chromosomes. Furthermore, we also determined that the chromosome 19p13.3 breakpoint occurred within the terminal 1 Mb region. This is the first report of a mosaic non-Robertsonian dicentric chromosome involving chromosomes 14 and 19 with the karyotype determined as 45,XX,dic(14;19)(p11.2;p13.3)[35]/46,XX[15], and we suggest that the chromosome rearrangement could be the cause of clinical phenotype.